State-of-the-art therapy for salpingo-oophoritis from the perspective of novel clinical guidelines - М.S. Selikhova; A.A. Smol'yaninov (LCC «Medicine-Inform», 2022)
M.S. Selikhova, A.A. Smol'yaninov Volgograd State Medical University, Volgograd, Russian Federation Abstract Pelvic inflammatory disease (PID) is an important issue due to its high occurrence in women of reproductive age and adverse effects on reproductive function. In 2021, the Ministry of Health of the Russian Federation had approved clinical guidelines that standardized management and treatment approaches to PID. These novel clinical guidelines focus on rational outpatient antimicrobial therapy using broad-spectrum medications. Treatment is prescribed empirically considering the predominant polymicrobial nature of PID. Opportunistic microbes (i.e., obligatory and facultative anaerobes) increasingly become causative agents of PID. Low titers of these microbes are found in the normal vaginal microflora, favoring broad-spectrum antibiotics effective against gram-positive and gram-negative bacteria. Treatment duration should be at least 10-14 days to completely eradicate the pathogen and prevent chronicity. Attention should be focused on choosing antibiotics with favorable safety p rofiles. Keywords: pelvic inflammatory disease, clinical guidelines, outpatient treatment, antibiotics, doxycycline, dispersible tablet, adherence. For citation: Selikhova M.S., Smol'yaninov A.A. State-of-the-art therapy for salpingo-oophoritis from the perspective of novel clinical guidelines. Russian Journal of Woman and Child Health. 2022;5(1):35-40 (in Russ.). DOI: 10.32364/2618-8430-2022-5-1-35-40.